Réponses

Meilleure réponse !
2014-09-10T22:42:35+02:00
A) P(x)=x²-4x+3 de la forme ax²+bx+c
Δ=b²-4ac=(-4)²-4*1*3=16-12=4
Les racines sont x1=(-b+√Δ)/2a et x2=(-b-√Δ)/2a
Soit x1=(4+2)/2=3 et x2=(4-2)/2=1
Donc P(x)=(x-3)(x-1)

b) P(x)=x²-2x+1
Δ=(-2)²-4*1*1=4-4=0 donc la racine est double
Soit x=2/2=1
Donc P(x)=(x-1)²

c) P(x)=3x²+1+4x=3x²+4x+1
Δ=4²-4*3*1=16-12=4
Soit x1=(-4+2)/6=-1/3 et x2=(-4-2)/6=-1
Donc P(x)=3(x+1/3)(x+1)

d) P(x)=-6x²+x+2
Δ=1-4*(-6)*2=1+48=49
Soit x1=(-1+7)/(-12)=-1/2 et x2=(-1-7)/(-12)=2/3
Donc P(x)=-6(x+1/2)(x-2/3)

e) P(x)=5x²+30x+45=5(x²+6x+9)=5(x+3)²
Racine double x=-3

f) P(x)=x²-5x-6
Δ=(-5)²-4*1*(-6)=25+24=49
Soit x1=(5-7)/2=-1 et x2=(5+7)/2=6
Donc P(x)=(x+1)(x-6)